Job morale: a scoping review of how the concept developed and is used in healthcare research - Alina Sabitova; Lauren M. Hickling; Stefan Priebe (BMC, 2020)
Abstract Background The job morale of healthcare staff is widely seen as an important factor for the quality of care. Yet, there are different understandings of what constitutes job morale, which hinders systematic research and comparisons. We therefore conducted a scoping review of how the concept of job morale has developed over time and how it is used in healthcare research. Methods A scoping review was conducted to identify relevant literature. Data were gathered on study design and context, objectives, definitions of morale, outcome measures and key findings. Data was synthesised using a descriptive analytical framework. Results Ninety-three unique studies met eligibility criteria for the present review. The literature outlines four main periods of the evolution of the concept of job morale: The First World War and the interwar years; Second World War; Aftermath of the Second World War; and Contemporary period. The concept of job morale originated in a military context and was later applied to and specified in the healthcare literature. The concept has been applied to individuals and groups. The understandings used in healthcare vary, but overlap. Methods for assessing job morale in healthcare include quantitative scales, indirect measurements of consequences and predictors of morale, and qualitative approaches. Existing studies have mainly focused on the job morale of general practitioners, nurses and mental health professionals in high-income countries. Conclusions Although the understandings of job morale in healthcare are heterogeneous and inconsistent, the concept appears to have been useful over longer periods of time and in different contexts. Which precise understanding of job morale is useful, depends on the given research purpose, and studies should make explicit which exact understanding they apply. Systematic research on job morale is required to facilitate measures to improve and maintain high levels of morale across different professional groups, including professionals in low- and middle-income countries.